2022
DOI: 10.14740/jnr721
|View full text |Cite
|
Sign up to set email alerts
|

Review of Huntington’s Disease: From Basics to Advances in Diagnosis and Treatment

Abstract: We conducted the present review facing the enormous growth of scientific knowledge in Huntington's disease (HD) and the need for a practical update for general neurologists. HD is a devastating neurodegenerative disease of autosomal dominant inheritance and full penetrance, caused by an expansion of the cytosine-adenine-guanine (CAG) trinucleotide in the huntingtin gene located on chromosome 4. The clinical phenotype varies according to the age of presentation, but it is mainly characterized by cognitive, moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The relationship between Huntington proteins and 14-3-3 proteins has garnered significant attention in the field of neurobiology. HD is a devastating neurological disorder characterized by the aggregation of mutant HTT and progressive neurodegeneration ( Rojas et al, 2022 ). Studies have revealed that mutant HTT interacts with various cellular proteins, including 14-3-3 proteins ( Shimada et al, 2013 ).…”
Section: Role Of 14-3-3 Proteins In Neurological Disordersmentioning
confidence: 99%
“…The relationship between Huntington proteins and 14-3-3 proteins has garnered significant attention in the field of neurobiology. HD is a devastating neurological disorder characterized by the aggregation of mutant HTT and progressive neurodegeneration ( Rojas et al, 2022 ). Studies have revealed that mutant HTT interacts with various cellular proteins, including 14-3-3 proteins ( Shimada et al, 2013 ).…”
Section: Role Of 14-3-3 Proteins In Neurological Disordersmentioning
confidence: 99%
“…These phenotypic markers can be observed in postmortem brain samples from patients or animal models [7]. The disease is accompanied by behavioral symptoms, for instance, impaired motor functions and disturbances of mental and cognitive abilities [8].…”
Section: Hd Mechanismsmentioning
confidence: 99%
“…This hereditary neurodegenerative disease is caused by cytosine–adenine–guanine (CAG) trinucleotide repeats in the first exon of the HTT gene that encodes Huntingtin (HTT). This mutation results in the production of mutant HTT (mHTT), which has an expanded polyglutamine (polyQ) domain near the N-terminus of the protein, due to an increase in the number of polyQ-encoding CAG repeats [ 1 , 2 , 3 , 4 ]. MHTT forms aggregates in the cytoplasm and nucleus of neurons and is associated with a cascade of pathogenic processes, including mitochondrial dysfunction, transcriptional dysregulation, altered protein homeostasis and synaptic dysfunction, which ultimately leads to neuronal cell death [ 2 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%